KOMUNIKASI KOTA HEXAGON DI MEDIA SOSIAL - Mariana Rista Ananda Siregar; Roni Jayawinangun (Universitas Djuanda Bogor, 2019)
City Branding is a autentity of a city and must managed properly, applied and become a culture and behavior for both the apparatus and the citizens of the city. In managing a city and establishing city branding, a strong research is required to map changes in the environment, the target market, the city's competitors and the changes that occur within the city itself. In addition to research, a combination of other communication and marketing strategies is important to consider the implementation of city branding. Based on the background, this research aims are to: first, to know the characteristics of citizen social media users in the city of Bogor, secondly, describing and analyzing the communication of the branding of Bogor, the third, explaining and analyzing Branding of the city of Bogor. The methods used in this study are descriptive analysis, and the rate of score. The results found in the study explained that the management of the city's branding could combine the strengths of primary and secondary communications in the city, especially on social media to elicit the sense of meaning a city refers to the model Branding of the city hexagon.